Lithium in drinking water and suicide prevention. (January 2015) - Vita, Antonio; De Peri, Luca; Sacchetti, Emilio
<x xml:space="preserve">Abstract</x> Suicide is a serious public health problem worldwide, and many nations are committed to developing prevention programmes to reduce the incidence of suicide. To date, several strategies have been proposed for suicide prevention, both at the population and at the individual level, some of which may be pharmacological. In particular, a substantial amount of data show that lithium significantly reduces mortality in patients with mood disorders. Initiating from this evidence, some recent studies have investigated whether a relationship might exist between levels of lithium in drinking water and mortality rates for suicide in the general population. We have systematically reviewed all the articles published on this issue to date. The available literature indicates that higher lithium levels in drinking water may be associated with reduced risk of suicide in the general population.